PERANCANGAN SISTEM INFORMASI LINIERITAS BIDANG STUDI PADA KEMENTERIAN PENDIDIKAN DAN KEBUDAYAAN - Nasril, Nasril; Aribah, Ghina (JURNAL LENTERA ICT, 2018)
AbstractThis study entitled "Design of Information Systems Division Linearity Studies in the Ministry of Education and Culture". The purpose of this study was to establish linearity Information Systems Field of Study At the Ministry of Education and Culture that serves to facilitate the search for information on subjects alignment with certification code that has been owned by teachers who have been certified. The results of this study are that the field linearity information system still uses a manual system or the data collection system still uses injection. In the process of linearity data collection, the resulting data often experiences duplicate data, and to replace the manual system, linearity is transformed into a computerized system.Keywords: Information Technology, Information System Design, Linearity.